2022
DOI: 10.1111/den.14420
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cold snare polypectomy: Current standard technique and future perspectives

Abstract: It has been shown that resection of adenomatous colorectal polyps can reduce mortality due to colorectal cancer. In daily clinical practice, simpler and safer methods of colorectal polypectomy have been sought to enable endoscopists to resect all detected lesions. Among these, cold snare polypectomy (CSP) is widely used in clinical practice because of its advantages in shortening procedure time, reducing delayed bleeding risk, and lowering treatment costs, while maintaining a similar complete resection rate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 68 publications
0
19
0
Order By: Relevance
“…This is important, as there have been an increasing number of studies reporting the application of CSP in lesions larger than 10 mm or even larger than 20 mm. 7 Because the risk of high-grade dysplasia (HGD) or invasive cancer increases along with size, an unclear horizontal or vertical margin may increase the risk of PCCRC. Though CSP does not apply electrocautery and reduces the likelihood of cautery effect affecting margin assessment, reconstruction of multiple tumor specimens after piecemeal CSP is still challenging, and failure of specimen retrieval may cause underdiagnosis of HGD or invasive cancer.…”
Section: Editorial: Optimizing the Success Of Cold Snare Polypectomy ...mentioning
confidence: 99%
See 3 more Smart Citations
“…This is important, as there have been an increasing number of studies reporting the application of CSP in lesions larger than 10 mm or even larger than 20 mm. 7 Because the risk of high-grade dysplasia (HGD) or invasive cancer increases along with size, an unclear horizontal or vertical margin may increase the risk of PCCRC. Though CSP does not apply electrocautery and reduces the likelihood of cautery effect affecting margin assessment, reconstruction of multiple tumor specimens after piecemeal CSP is still challenging, and failure of specimen retrieval may cause underdiagnosis of HGD or invasive cancer.…”
Section: Editorial: Optimizing the Success Of Cold Snare Polypectomy ...mentioning
confidence: 99%
“…Histopathological studies have shown that CSDPs are in the muscularis mucosa, and it may be an indicator of incomplete resection and is often associated with specimen fragmentation. 7 In this issue of Journal of Gastroenterology and Hepatology, Horii et al performed a randomized controlled study and reported that CSP using a thinner diameter of snare wire could achieve a significantly higher histological complete resection rate compared with that using a normal-diameter snare (70% vs 81%, P = 0.04). 9 In a subanalysis of results based on level of experience, it is noteworthy that more experienced endoscopists appeared to have a higher complete resection rate than trainees.…”
Section: Editorial: Optimizing the Success Of Cold Snare Polypectomy ...mentioning
confidence: 99%
See 2 more Smart Citations
“…8 The technique to resect polyps should be easy, safe, and effective; hence, cold snare polypectomy (CSP) is becoming the first choice for the resection of small polyps. 9 Several reports have demonstrated increased safety of CSP for small polyps compared to hot snare polypectomy. 10,11 It was hypothesized that starting diet immediately after the resection of colorectal polyps would increase the risk of delayed bleeding.…”
Section: Introductionmentioning
confidence: 99%